Digital transformation in management and accounting: Implications for MSME performance - Muhammad Distian Andi Hermawan; Huda, Irham Miftahul (Review of Management, Accounting, and Business Studies, 2026)
This study aims to comprehensively examine research trends related to digital transformation in the fields of management and accounting, as well as analyse its impact on the business performance of micro, small and medium enterprises (MSMEs). A Systematic Literature Review (SLR) approach was used to synthesise and critically evaluate findings from previous empirical and conceptual studies. The reviewed articles were selected from leading academic databases to ensure the credibility and relevance of the sources. To enhance methodological transparency and rigour, the review process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, including the stages of identification, screening, eligibility, and inclusion The articles included cover the last eight years, in order to enhance the credibility and comparability of the analysis. The findings indicate that digital transformation in management functions plays an important role in improving operational efficiency, improving the quality of managerial decision-making, and increasing organisational flexibility and adaptability in a dynamic business environment. On the other hand, digital transformation in accounting practices such as the adoption of digital accounting systems, cloud-based software, and automated reporting contributes to the accuracy, transparency, and timeliness of financial information, which supports better financial control and strategic planning. However, the impact of digital transformation on SME performance is uneven, n=30 articles included. This depends heavily on internal readiness factors, including digital literacy levels, human resource competencies, technological infrastructure, and strong managerial commitment. Furthermore, this review identifies several key barriers faced by MSMEs in implementing digital transformation, such as limited financial resources, lack of technical expertise, and resistance to organisational change. This study also highlights existing research gaps, particularly the limited integration of management and accounting perspectives in analysing digital transformation. Overall, these findings contribute theoretically to the literature on digital transformation and SME performance, and offer practical insights for policymakers and practitioners in formulating effective SME development strategies in the digital era.